The marketing of tourism services using the internet: A resource-based view - R. Elliott; C. Boshoff (South African Journal of Business Management, 2009)
Taking a resource-based view of the business, this study attempts to identify the non-technology resources driving the successful use of the Internet for marketing tourism services. If these complementary resources can be identified, they can be used to leverage the use of the Internet for marketing, which in turn will contribute to a sustainable competitive advantage for small tourism businesses.Hypotheses are developed and then tested by making use of a large-scale empirical study. The results indicate that a network of effective alliances, the existence of a product champion in the business, and appreciation by the owner-manager of the broader business implications surrounding the implementation of the Internet for marketing, are important to the successful use of the Internet for the marketing of tourism services.The study makes a contribution to the literature by identifying and measuring the drivers of Internet marketing success, as well as by establishing how resource-based theory provides a valuable approach to consideration of how these factors can be managed.
Keywords: 650